Do School Principals Respond to Increased Public Scrutiny? New Survey Evidence from Australia - Michael Coelli; Gigi Foster; Andrew Leigh (Institute of Labor Economics (IZA), 2018)
We explore responses of Australian school principals to the introduction of test score reporting via the My School website in 2010. Our analysis is motivated by the implicit assumption that heightened public scrutiny should motivate principals to align schools' policies and practices with what is believed to generate better test results. We use responses from both public and private schools to a custom-built questionnaire administered to principals before (2009) and after (2012) the My School website launch. We find scarce evidence of meaningful adjustments over time, but we do find evidence of significantly different policies and practices across school groups.
Keywords: D83; I21; I28; 330; school accountability; standardized test scores; educational performance; school competition